Contribuições ao controle aplicado a uma topologia híbrida para regulação de tensão em geradores de indução autoexcitados - Tischer, Celso Becker (2017)
This doctoral thesis presents contributions to control applied to hybrid topology for voltage regulation of self-excited induction generators in stand-alone microgeneration systems. The generator system considers a three-phase bus composed by a distribution static synchronous compensator (DSTATCOM), excitation capacitors bank and switchable capacitor banks connected in parallel to electrical power supply system. The switchable capacitor banks provides the most part of the reactive power for system and the DSTATCOM is controlled to provide the difference between the reactive power supplied by excitation capacitors bank and reactive power required by induction generator and aggregated loads, besides to compensate harmonic component of non-linear loads. To accomplish that, a control strategy performed by a dual loop is proposed, two inner current loop is composed by proportional-resonant controllers and two outer voltage loop composed by proportional-integral controllers. Furthermore, in this work, the frequency control is performed by an electronic load (ELC) connected to the AC bus system through non-controlled three-phase rectifier. An algorithm to control as well as the design procedure for switchable capacitor banks is presented. Simulation and experimental results are presented to demonstrate the performance of the current, voltage and frequency controllers and the operation response of switchable capacitor banks.